Analysis of Risk Factors with the Degree of Pelvic Organs Prolapse at Dr. Mohammad Hoesin General Hospital Palembang - Hadrians Kesuma Putra; Callista Zahra Aidi; M. Zulkarnain (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Pelvic organ prolapse (POP) is a condition in which one or more pelvic organs (consisting of the uterus, vaginal cuff, bladder, intestines, and rectum) or more are still in or out of the vagina. Risk factors that influence the incidence of POP consist of obstetric risk factors (number of parity and birth method) and non-obstetric risk factors (age, menopause, BMI, comorbid disease, and hypertension). The purpose of this study was to analyze the risk factors associated with the degree of POP. Methods. This study is an observational study with a cross-sectional approach to 111 patients examined at the Department of Obstetrics and Gynecology, Dr. Mohammad Hoesin general hospital Palembang on January 2017 to December 2019, who was diagnosed with pelvic organ prolapse. Results. The results showed the effect of variables with the degree of POP using the chi-square test, consisting of parity (p=0.007), birth method (p=<0.001), age (p=0.016), menopause (p=0.001), BMI (p =0.005), indicates that there is a significant effect on the degree of POP. Meanwhile, comorbid factors (p=0.481) and hypertension (p=0.415) did not show a significant relationship with the degree of POP. The results of the binary logistic regression analysis of all risk factors, the number of parity >4, overweight, and age 40 years, will have a 99.85% chance of experiencing grade 3 or 4 prolapse. Conclusion. Age is the most dominant risk factor affecting the degree of pelvic organ prolapse, with 19 times the chance of developing POP 3 or 4 degrees.